An Esophagogastroduodenal Crohn’s-Like Disease in a Long-Standing Pan-Ulcerative Colitis Patient - Christopher Moore; Shriram Jakate; Ali Keshavarzian (Case Reports in Gastrointestinal Medicine)
Inflammatory bowel disease (IBD) comprises the principal subtypes Crohn’s disease (CD) and ulcerative colitis (UC), with a fraction remaining as IBD unclassified (IBDU). Given the complexity of IBD manifestations in a patient over time and our increasing understanding of IBD biology, a modification in subtype diagnosis can also occur. Herein is a case of a 27-year-old female with well-controlled and long-standing pan-UC, who developed Crohn’s-like esophagogastroduodenitis. The difficulty in classifying IBD into a single traditional subtype, and the debated presentation of a coexistent IBD will be discussed.